Synthesis of new pyridines with sulfonamide moiety via a cooperative vinylogous anomeric-based oxidation mechanism in the presence of a novel quinoline-based dendrimer-like ionic liquid. Issue 5 (22nd January 2021) - Torabi, Morteza; Yarie, Meysam; Zolfigol, Mohammad Ali; Rouhani, Shamila; Azizi, Shohreh; Olomola, Temitope O.; Maaza, Malik; Msagati, Titus A. M.
Abstract : In the present study, we reported the synthesis of a novel quinoline-based dendrimer-like ionic liquid and investigated its catalytic performance for the synthesis of new pyridines with sulfonamide moieties via a cooperative vinylogous anomeric-based oxidation mechanism. Abstract : In the present study, we reported the synthesis of a novel quinoline-based dendrimer-like ionic liquid. After characterization of the mentioned ionic liquid with suitable techniques such as Fourier transform infrared spectroscopy (FT-IR), energy dispersive X-ray spectroscopy (EDX), elemental mapping, thermogravimetric analysis (TGA) and derivative thermogravimetry (DTG), its catalytic performance was investigated in the synthesis of new pyridines with sulfonamide moiety via a cooperative vinylogous anomeric-based oxidation mechanism under mild reaction conditions. All target molecules were achieved in short reaction times and high yields.